TEA LEAF ASSISTED SYNTHESIS OF SILVER NANOPARTICLES AND THEIR ANTIMICROBIAL POTENTIAL - LIPI GOSWAMI; DEBABRAT BAISHYA; SORRA SANDHYA; JOYEETA TALUKDAR; PRANAYEE DATTA (International Journal of Pharma and Bio Sciences, 2014)
Synthesis of silver nanoparticles in fresh tea leaves extract has been carried out in this work as an environment friendly approach and to explore its antimicrobial potential. The formation of silver nanoparticles is characterized by UV-Vis spectra. The average size of the nanoparticles, the value of the d-spacing has been revealed by the data obtained from HR-TEM and XRD. Synthesized nanoparticles have then been examined for biopotential against different pathogenic bacterial strains viz. E. coli, Enterobacter aerogen, Staphylococcus aureus and Salmonella typhi, by the disk diffusion method. It has been confirmed from the diameter of the zone of inhibition that the tea extract has no effect of its own on bacterial strains as such, but silver nanoparticles capped tea extracts exhibited prominent antibacterial activity.